2014
DOI: 10.1177/0022034514536731
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Services by Medical and Dental Providers and Treatment Outcomes

Abstract: Objective: Nearly all state Medicaid programs reimburse nondental primary care providers (PCPs) for providing preventive oral health services to young children; yet, little is known about how treatment outcomes compare with children visiting dentists. This study compared the association between the provider of preventive services (PCP, dentist, or both) with Medicaid-enrolled children before their third birthday and subsequent dental caries-related treatment (CRT) and CRT payment. Methods: We conducted a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Positive outcomes included enhanced interprofessional collaboration, satisfaction of non-dental primary care providers with the oral health care training, increased performance of non-dental care providers, and patient satisfaction with care delivery [ 50 52 , 54 , 56 , 58 61 , 64 , 66 – 69 ]. Objective outcomes included an increase in the number of trained non-dental health care providers, the number of dental visits, screening and preventive acts, referrals, as well as a decrease in the percentage of patients’ dental treatment non-attendance and finally improved access to dental care [ 12 , 49 52 , 54 , 55 , 60 , 69 , 70 , 72 , 73 ]. Haughney et al (1998) reported on the follow-up of a co-located model of integrated care and demonstrated that after three years, the total number of medical/dental visits as well as dental visits by the 0–5 year age group and by the elderly increased by 90%, 32% and 24%, respectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Positive outcomes included enhanced interprofessional collaboration, satisfaction of non-dental primary care providers with the oral health care training, increased performance of non-dental care providers, and patient satisfaction with care delivery [ 50 52 , 54 , 56 , 58 61 , 64 , 66 – 69 ]. Objective outcomes included an increase in the number of trained non-dental health care providers, the number of dental visits, screening and preventive acts, referrals, as well as a decrease in the percentage of patients’ dental treatment non-attendance and finally improved access to dental care [ 12 , 49 52 , 54 , 55 , 60 , 69 , 70 , 72 , 73 ]. Haughney et al (1998) reported on the follow-up of a co-located model of integrated care and demonstrated that after three years, the total number of medical/dental visits as well as dental visits by the 0–5 year age group and by the elderly increased by 90%, 32% and 24%, respectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…; Kranz et al. ). Because dental caries often takes many months to progress to a point at which restorative care is required, studies that used a shorter length may not capture as much downstream treatment costs.…”
Section: Discussionmentioning
confidence: 98%
“…4 ). S. mutans , which usually grows as a biofilm, is a significant periodontal pathogen responsible for dental caries, a condition that lacks effective therapeutic options 49 . Significantly, many lysins active against planktonic streptococci and staphylococci have also been reported to be highly active against their biofilms, such as the ClyR CD donor, PlyC 50 , and the ClyR CBD donor, PlySs2 51 .…”
Section: Discussionmentioning
confidence: 99%